Disney’s “war efforts”: the lion king and Education for death, or Shakespeare made easy For your apocalyptic convenience - Alfredo Michel Modenessi (Ilha do Desterro)
“‘Peace, ho! Brutus speaks.’ And speaks. And speaks. And except for a couple of fatal blows that he somewhat misplaces in the bodies of his “best lover[s]” (i.e. Caesar and himself), he hardly does anything but deliver speeches. Worse, he hardly ever listens—either to himself or to his “other-selves” Portia and Cassius (a.k.a. “your glass”). Or maybe he does a bit, when it’s too late and the only course of action left is assisted self-slaughter, seasoned with a characteristically Shakespeare-ironic request to Caesar’s equally narcissistic spirit: “now be still!” “With himself at war,” the self appointed hero of Shakespeare’s Julius Caesar suffers from, and dies of, common symptoms of self-deception.